"Sisters with Voices": A Study of the Experiences and Challenges Faced by Black Women in London Baptist Association Church Ministry Settings. Issue 3 (November 2015) - Mahon, Michele
Abstract : This research investigates the experiences of women, predominantly, Black women mainly of African and Caribbean heritage, in London Baptist church ministry contexts connected with the London Baptist Association. Drawing from principles discovered in liberation theology, Black theology, feminist theology and womanist theology, a unique perspective is presented from these women's experiences, firmly rooted in their context and spirituality. There are over 300 churches represented by the LBA. Forty-two women are currently listed as ministers by the LBA and they were approached by email to answer the research questions via an online survey. What was discovered is that on the whole these ministers are thriving in their unique ministry contexts and find creative ways to fulfil their calling. They face many challenges, however, including isolation, lack of social capital, sexism and a lack of relevant information to help them progress in life and ministry. A number of suggestions are made to support these pioneering women in ministry.